2011
DOI: 10.1111/j.1532-5415.2011.03724.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Versus Drug Treatment for Overactive Bladder in Men: The Male Overactive Bladder Treatment in Veterans (MOTIVE) Trial

Abstract: Behavioral and antimuscarinic therapy are effective when added to alpha-blocker therapy for OAB in men without outlet obstruction. Behavioral treatment is at least as effective as antimuscarinic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 38 publications
1
75
0
1
Order By: Relevance
“…The literature provides clear support for the effectiveness of both bladder and behavioral training. 11,12 The literature supports the positive effects of weight loss on incontinence specifically. A relatively minor weight loss of 8% in obese woman reduced overall incontinence episodes per week and urgency urinary incontinence episodes by 47 and 42% vs. 28 and 26% in controls.…”
Section: Grade B)mentioning
confidence: 88%
“…The literature provides clear support for the effectiveness of both bladder and behavioral training. 11,12 The literature supports the positive effects of weight loss on incontinence specifically. A relatively minor weight loss of 8% in obese woman reduced overall incontinence episodes per week and urgency urinary incontinence episodes by 47 and 42% vs. 28 and 26% in controls.…”
Section: Grade B)mentioning
confidence: 88%
“…Burgio et al conducted a randomized controlled trial (RCT) of 143 men with bladder outlet obstruction (BOO) and OAB who had failed alpha-blocker therapy. 10 Patients were assigned to 8 weeks of behavioral therapy or oxybutynin. Behavioral therapy reduced nocturia by 0.7 voids per night, as compared with 0.32 voids per night for oxybutynin (P ¼ .05; LOE 3).…”
Section: Conservative Managementmentioning
confidence: 99%
“…Equivalence analysis was performed and indicated that posttreatment means were equivalent. There was a significantly greater reduction in nocturia and maximum urgency scores in the behavioral therapy and anticholinergic group, respectively [33].…”
Section: Behavioral Therapymentioning
confidence: 87%